A Structured Checklist Approach to Evaluating Transparency and Privacy in Brazilian Digital Services - Azevedo, Luciano Franceschi De; Canedo, Edna Dias (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.14996, 2025)
Context: The digitalization of public services in Brazil has improved access and efficiency, but has also raised concerns about transparency, privacy, and data protection. Despite the regulatory framework established by the Brazilian General Data Protection Law (LGPD), many services still lack clear communication and support for citizens regarding how their data is handled. Objective: This study aims to evaluate the trustworthiness of digital public services in Brazil, from the perspective of an ordinary citizen, by analyzing the alignment between declared privacy practices and actual data handling behaviors, as well as the accessibility of support provided to citizens in exercising their data protection rights. Method: We developed and applied a structured evaluation checklist based on three dimensions: (i) Declared Information Quality (QID), (ii) Factual Precision (PF), and (iii) Accessibility Support (AS). Five widely used federal services were selected and analyzed through manual inspection of public documentation, service behavior, and availability of support channels. Each item was scored based on predefined criteria, and qualitative observations were recorded to complement the analysis. Results: The overall average score across all services was 44.76%, with the best performance in factual precision (77.14%) and the worst in privacy support (20.00%). Only one service—“Conta Gov”—achieved a score above 50%. Transparency deficits were common, especially in the disclosure of sensitive data handling and the availability of dedicated support channels or Data Protection Officers (DPOs). Conclusion: The study reveals that while several services functionally comply with privacy expectations, most fail to communicate this effectively to users. The absence of accessible and explicit privacy declarations, combined with limited support mechanisms, undermines citizens’ ability to exercise their rights and reduces trust in digital government services. Our findings highlight the need for standardized privacy documentation and specialized support channels, reinforcing the importance of transparency as a critical component of software quality in the public sector.